Understanding how health systems facilitate primary care redesign. (7th December 2020) - Harvey, Jillian B.; Vanderbrink, Jocelyn; Mahmud, Yasmin; Kitt‐Lewis, Erin; Wolf, Laura; Shaw, Bethany; Ridgely, M. Susan; Damberg, Cheryl L.; Scanlon, Dennis P.
Abstract: Objective: To understand how health systems are facilitating primary care redesign (PCR), examine the PCR initiatives taking place within systems, and identify barriers to this work. Study Setting: A purposive sample of 24 health systems in 4 states. Study Design: Data were systematically reviewed to identify how system leaders define and implement initiatives to redesign primary care delivery and identify challenges. Researchers applied codes which were based on the theoretical PCR literature and created new codes to capture emerging themes. Investigators analyzed coded data then produced and applied a thematic analysis to examine how health systems facilitate PCR. Data Collection: Semi‐structured telephone interviews with 162 system executives and physician organization leaders from 24 systems. Principal Findings: Leaders at all 24 health systems described initiatives to redesign the delivery of primary care, but many were in the early stages. Respondents described the use of centralized health system resources to facilitate PCR initiatives, such as regionalized care coordinators, and integrated electronic health records. Team‐based care, population management, and care coordination were the most commonly described initiatives to transform primary care delivery. Respondents most often cited improving efficiency and enhancing clinician job satisfaction, as motivating factors for team‐based care. Changes in payment and risk assumption as well as community needs were commonly cited motivators for population health management and care coordination. Return on investment and the slower than anticipated rate in moving from fee‐for‐service to value‐based payment were noted by multiple respondents as challenges health systems face in redesigning primary care. Conclusions: Given their expanding role in health care and the potential to leverage resources, health systems are promising entities to promote the advancement of PCR. Systems demonstrate interest and engagement in this work but face significant challenges in getting to scale until payment models are in alignment with these efforts.